Resepsi Audiens Terhadap Transgender dalam Film Dokumenter Bulu Mata - Kevi Restu Pradhita; Fajar Junaedi (CHANNEL: Jurnal Komunikasi, 2019)
Film is one of the mass communication media that is e ective in disseminating information that aims to convey messages to the public. One documentary lm entitled Bulu Mata tells how transgender life is in a region that ill upholds Islamic law. Transgender is a person who has a gender identity that is di erent from his original gender. In Indonesia, transgender is ill a taboo thing in society and is considered a negative behavior. This study aims to nd out how the audience’s reception of transgender in a documentary entitled Bulu Mata. The theory used in this research is the theory of audience reception from Stuart Hall. This study uses a qualitative descriptive approach method and data collection techniques using in-depth interview method. In this study, it was successful to show audience receptions in interpreting Bulu Mata lms very di erently. Informants with backgrounds who are intere ed in gender issues are in a dominant position, informants with backgrounds that follow Kine’s lm organization are in negotiated positions, and informants who follow Rohis organizations are in oppositional positions.